Macroscopic technique for the evaluation of oral tongue tumour thickness: a reliable intraoperative method. Issue 8 (August 2016) - Pandey, M.; Vidhyadharan, S.; Puthalath, U.; Veeraraghavan, R.; Sukumaran, S.V.; Prasad, C.; Iyer, S.; Thankappan, K.
Abstract: There is no reliable method to assess tumour thickness preoperatively or intraoperatively in cases of oral tongue squamous cell carcinoma (SCC). The purpose of this study was to evaluate the efficacy of a macroscopic technique to measure tumour thickness. This was a prospective study of 51 consecutive patients with T1/T2 primary SCC of the oral tongue. All patients underwent primary resection with ipsilateral neck dissection. Thickness measurements were obtained using Vernier calipers on the fresh specimen. The technique was correlated with the microscopic evaluation statistically using (1) Pearson's correlation coefficient, (2) intra-class correlation, and (3) Bland–Altman plot with 95% confidence intervals. On comparing the macroscopic technique to the microscopic evaluation, Pearson's correlation ( r ) was 0.915 ( P  < 0.001). The inter-rater reliability using the intra-class correlation coefficient was 0.955. The Bland–Altman plot to test the agreement between the techniques showed the average difference between macroscopic thickness and microscopic thickness (bias) to be −0.421, with 95% limits of agreement of −3.166 and 2.82. There was a significant correlation and agreement between the macroscopic and microscopic measures of tumour thickness. The macroscopic technique could be used as a reliable tool to measure tumour thickness intraoperatively, prior to neck dissection.